Effect of heartfulness meditation on burnout, emotional wellness, and telomere length in health care professionals. Issue 1 (2nd January 2017) - Thimmapuram, Jayaram; Pargament, Robert; Sibliss, Kedesha; Grim, Rodney; Risques, Rosana; Toorens, Erik
ABSTRACT: Background : Burnout poses significant challenges during training years in residency and later in the career. Meditation is a tool to treat stress-related conditions and promote wellness. Telomere length may be affected by burnout and stress. However, the benefits of meditation have not been fully demonstrated in health care professionals. Objective : We assessed the effects of a 12-week 'Heartfulness Meditation' program on burnout, emotional wellness, and telomere length in residents, faculty members, and nurses at a large community teaching hospital during the 2015–16 academic year. Methods : All subjects completed a baseline Maslach Burnout Inventory (MBI) and Emotional Wellness Assessment (EWA) at the beginning of the study. Meditators received instructions in Heartfulness Meditation. At week 12, subjects completed a follow up MBI and EWA scores. Salivary telomere length was measured at baseline and week 12. Results : Twenty-seven out of a total 155 residents (17.4%) along with eight faculty physicians and 12 nurses participated in the study. Thirty-five enrolled as meditators and 12 as controls. At 12 weeks, the meditators had statistically significant improvement in all measures of burnout and in nearly all attributes of EWA. Controls showed no statistically significant changes in either burnout or emotional wellness scores. Relative telomere length increased with statistical significance in a younger subset of meditators. Conclusion : Our results indicate that meditation offers an accessible and efficient method by which physician and nurse burnout can be ameliorated and wellness can be enhanced. The increased telomere length is an interesting finding but needs to be confirmed with further research. Abbreviations : EWA: Emotional wellness assessment; MBI: Maslach burnout inventory; EE: Emotional exhaustion; DP: Depersonalization; PA: Personal accomplishment; PI: Prinicipal investigator; JT: Jayaram Thimmapuram